Career calling and safety behavior among nurses: a cross-sectional study based on latent profile analysis - Linli Xie; Sijia Xie; Yan Yu; Jie Jing; Min Shi; Lingli Dai (Frontiers in Psychology)
ObjectiveThis study aimed to clarify the subgroups of career calling among Chinese nurses, explore the factors correlated with the subgroups, and investigate the relationship between nurse safety behavior and different profiles of career calling.MethodsA cross-sectional study of 2,567 nurses from 25 hospitals in China was conducted from February to September 2023. A latent profile model of nurses’ career calling was analyzed using Mplus 7.4. The influencing factors of each profile were analyzed by multinomial logistic regression analysis. The hierarchical regression analysis was used to examine the relationship between nurse safety behavior and different profiles of career calling. The STROBE guidelines were followed in this research.ResultsThree distinct latent profiles were identified: “low-calling” type (12.4%), “medium-calling” type (54.4%), and “high-calling” type (33.2%) groups, respectively. Gender and number of night shifts per month were identified as factors influencing the latent profiles of nurses’ career calling. The different categories of career calling significantly predicted the nurse safety behavior (ΔR2 = 0.307, p < 0.001).ConclusionThis study suggests that nurses experience different types of career calling. The different categories of career calling are significantly associated with the nurse safety behavior. Consequently, administrators should pay attention to the differences in individual career calling and develop targeted intervention strategies to facilitate nurses’ career calling based on the influences of the different underlying profiles and develop enhancement strategies to strengthen nurses’ safety behaviors to ensure patient safety.